2014
DOI: 10.5194/gtes-2-1-2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of major fault zones on 3-D coupled fluid and heat transport for the Brandenburg region (NE German Basin)

Abstract: Abstract.To quantify the influence of major fault zones on the groundwater and thermal field, 3-D finiteelement simulations are carried out. Two fault zones -the Gardelegen and Lausitz escarpments -have been integrated into an existing 3-D structure of the Brandenburg region in northeastern Germany. Different geological scenarios in terms of modelled fault permeability have been considered, of which two end-member models are discussed in detail. In addition, results from these end-member simulations are compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 34 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Such phenomena have already been described for other basins in different tectonic settings (Bayer et al 1997;Allen and Allen 2005;Stephenson et al 2009;Noack et al 2010;Cherubini et al 2014) and are laterally influencing each other. For the Alps and the Molasse Basin this implies that the heat coming from the asthenosphere together with the heat generated in the crystalline crust arrives at the base of the insulating sediments of the Alpine Body and the Molasse Basin, is stored within the sediments and causes higher temperatures within the latter.…”
Section: Regional Thermal Effectsmentioning
confidence: 90%
“…Such phenomena have already been described for other basins in different tectonic settings (Bayer et al 1997;Allen and Allen 2005;Stephenson et al 2009;Noack et al 2010;Cherubini et al 2014) and are laterally influencing each other. For the Alps and the Molasse Basin this implies that the heat coming from the asthenosphere together with the heat generated in the crystalline crust arrives at the base of the insulating sediments of the Alpine Body and the Molasse Basin, is stored within the sediments and causes higher temperatures within the latter.…”
Section: Regional Thermal Effectsmentioning
confidence: 90%
“…Ascending warmer fluid in the area of the positive thermal anomalies and descending colder fluid in the area of the negative thermal anomalies driven by density gradients within the faults caused insignificant (1-5 K) local cooling which did not lead to changes in the general temperature trend. Such a limited spatial influence of permeable fault zones on the regional thermal field has been already described by Cherubini et al (2014). However, an implementation of permeable fault zones into reservoir-scale models might still be of high importance for the local temperature.…”
Section: Discussionmentioning
confidence: 99%
“…3) as described before. Accordingly, high hydraulic conductivities prevail in the northern and eastern-most model parts, and Like the layers, all faults have been characterized with hydraulic properties following Schulz and Thomas (2012) and Cherubini et al (2014). Thereby, a hydraulic conductivity much higher than of any other layer of the model was assumed for the faults to open permeable fluid flow paths.…”
Section: Parameterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the regional hydrodynamics, previous studies have identified the URG as a regional discharge valley. The main recharge is thought to occur along the graben flanks (Black Forest, Vosges Mountains and Odenwald) with groundwater discharging preferentially within the graben itself (Clauser and Villinger, 1990;Freymark et al, 2019;Guillou-Frottier et al, 2013;Lampe and Person, 2002;Pribnow and Clauser, 2000). Indeed, the deepest topographic point (also the lowest elevation of the hydraulic head) is found in the northern domain within the federal state of Hesse.…”
Section: Introductionmentioning
confidence: 99%